To determine and examine the prospect and feasibility study of anti-cancer drugs for local production in Bangladesh - Islam, Mohd Aminul; Azad, Abdul Kalam (AENSI Publications, 2013)
The objective of this study was to find the feasibility of producing demandable Anti-Cancer drugs in Bangladesh. Anti-Cancer Drugs has been a common import item in Bangladesh for the previous years. This takes a lot of foreign currency to import the necessary item from the outside world and produce a negative impact on the national economy of Bangladesh. Thus we can decide to produce Anti-Cancer Drugs which is in great demand in our country. And for this, this project is concerned for producing ‘Anti-Cancer Drugs’. ‘Anti-Cancer Drugs’ has a good demand in the market and nearly 95% to 98% pharmaceutical companies are used to import this product from the foreign countries (according to anti-cancer Market). This project will use its full capacity to meet the demand in the market. The project will also offer reasonable price to the customers to capture the whole market maintaining the international quality of the product, so that the customers need not to compromise with the product quality. All the required machinery of this project will be imported from foreign countries ones which will cost nearly TK. 218020000/-(2,800,342.69 USD). All the machineries that will be used are easy to operate and the spare parts of the machineries can be obtained very easily from the suppliers and some are available in local market also. Production process of this product will involve automatic technology and the proposed project will start in its own plant. Required raw materials for the proposed product will be acquired from foreign sources at a reasonable price. To make the project a successful one all the employees should be committed. There will be a project coordinator who will control and monitor the entire project and with him there will also be a supervisor to take care of the operations of the project. The proposed project will generate revenue of TK. 2057305378/- (26,425,030.15 USD) in the first year and after the first year it will give an Earning before Tax (EBT) of TK. 1674558258/-(21,508,858.86 USD). The project seems feasible to go to production of the proposed anti-cancer products and prospect will be bright.